Back Cover: Advanced Engineering Materials 6∕2018. Issue 6 (21st June 2018) - Unknown
Abstract : The cover image shows the tensile property enhanced by Pr‐doping in contrast to strainstress curves, and fracture morphology of both side & front views exhibiting crack extension and shear deformation regions of Cu‐based wires. In nature, this improved tensile behavior is attributed to strengthened interaction of shear bands and vein shaped pattern forming. Further details can be found in the article1700935 by Jingshun Liu and co‐workers.